Flexible and Tough Superelastic Co–Cr Alloys for Biomedical Applications. Issue 27 (3rd June 2022) - Odaira, Takumi; Xu, Sheng; Hirata, Kenji; Xu, Xiao; Omori, Toshihiro; Ueki, Kosuke; Ueda, Kyosuke; Narushima, Takayuki; Nagasako, Makoto; Harjo, Stefanus; Kawasaki, Takuro; Bodnárová, Lucie; et al.
Abstract: The demand for biomaterials has been increasing along with the increase in the population of elderly people worldwide. The mechanical properties and high wear resistance of metallic biomaterials make them well‐suited for use as substitutes or as support for damaged hard tissues. However, unless these biomaterials also have a low Young's modulus similar to that of human bones, bone atrophy inevitably occurs. Because a low Young's modulus is typically associated with poor wear resistance, it is difficult to realize a low Young's modulus and high wear resistance simultaneously. Also, the superelastic property of shape‐memory alloys makes them suitable for biomedical applications, like vascular stents and guide wires. However, due to the low recoverable strain of conventional biocompatible shape‐memory alloys, the demand for a new alloy system is high. The novel body‐centered‐cubic cobalt–chromium‐based alloys in this work provide a solution to both of these problems. The Young's modulus of <001>‐oriented single‐crystal cobalt–chromium‐based alloys is 10–30 GPa, which is similar to that of human bone, and they also demonstrate high wear and corrosion resistance. They also exhibit superelasticity with a huge recoverable strain up to 17.0%. For these reasons, the novel cobalt–chromium‐based alloys can be promising candidates for biomedical applications. Abstract : A novel developed Co–Cr‐based biomaterial not only has a low Young's modulus (10–30 GPa) similar to human bone, but also a high wear resistance, disrupting the trade‐off relation in conventional metallic biomaterials. The thermoelastic martensitic transformation of these alloys allows a huge recoverable superelastic strain up to 17.0%, which is twice that of commercial Ti–Ni.